Experiences and perceptions of birth companions supporting women in labour at a District Hospital in Limpopo, South Africa - Joy V. Summerton; Tsakani R. Mtileni; Maphei E. Moshabela (AOSIS, 2021)
Background: South Africa has included birth companions in its national guidelines for maternity care and the revised Maternity Case Record, in and effort to improve the quality and experience of care. However, reservations amongst healthcare providers remain about the acceptability of birth companions in the labour ward. Objectives: To document the experiences and perceptions of birth companions who supported women in labour in a rural hospital in Limpopo Province where a Respectful Maternity Care (RMC) project was piloted. Method: An institution-based cross-sectional study design was employed. Purposive sampling was employed where all birth companions who supported a woman during labour and birth were included in the study. The experiences and perceptions of birth companions were captured using a birth companion feedback book during the period of 1st April to 30th August 2019. Thematic analysis was used to analyse the data. Results: Seventy-one (71) of the 73 birth companions only had positive responses about the birthing experience and how both the birth companion and woman in labour were treated. Two birth companions were dissatisfied with the treatment provided by the midwife that supported the birth. Conclusion: It is important for healthcare providers to understand the far reaching emotional and psychological impact of their attitudes and behaviour on, not only women in labour but also on others who witness their (healthcare providers) behaviour. Mechanisms to obtain feedback from birth companions should be integrated into strategies to improve the quality and experience of care for women during childbirth.